Evaluation of exotic Lettuce (Lactuca sativa L.) genotypes for the growth & yield attributes under agro-ecological conditions of Tandojam (Journal of Agriculture and Biology, 2025)
Lettuce (Lactuca sativa L.) is a cool season green leafy vegetable belonging to the Composite family. It is very nutritious and a rich source of vitamin C, minerals and fiber and is commonly consumed in salad mixes. The field-based study was conducted during Winter 2023-24, at Experimental Area of Plant Breeding and Genetics Department, Sindh Agriculture University, Tandojam. following randomized complete block design. For present study three genotypes viz: green leaf lettuce, Italic Lettuce and Red Green Dragon Lettuce were used to evaluate their growth, yield and physiological traits. The substantial variation was observed for all the traits investigated. The maximum Chlorophyll Content (47.42 SPAD) was recorded in Red Green Dragon Lettuce variety, whereas the minimum chlorophyll content (30.54 SPAD) was recorded in Italic Lettuce. The maximum plant spreading (46.32 cm) was recorded in green leaf lettuce variety, whereas the minimum plant spreading (31.01 cm) was recorded in Red Green Dragon Lettuce variety. The green leaf lettuce variety showed maximum width of leaf (15.31 cm), whereas the minimum width of leaf (4.49 cm) was recorded in Red Green Dragon Lettuce variety. The Red Green Dragon Lettuce variety produced maximum Length of Leaves (24.55 cm), Plant Height (25.32 cm) and root depth (12.03 cm), whereas the minimum Length of Leaves (11.51 cm), Plant Height (12.46 cm) and Root Depth (9.87cm) was recorded in Italic Lettuce. The Maximum leaf yield was recorded in Green Leaf Lettuce followed by Red Green Dragon Lettuce. It is recommended that for obtaining higher leaf yield Green Leaf Lettuce may be grown under agro-ecological conditions of Tandojam.